The voices of malcolm X As An African American Muslim in the black revolution speech: A discourse analysis - Sekar Tanjung Nawang Kesturi (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2019)
etik,1/irh,c.1